The use of IT tools for knowledge management in companies - Michal Cupial; Anna Szelag-Sikora; Jakub Sikora; Joanna Rorat; Marcin Niemiec (Institute of Economic Research (IER), 2017)
Research background: Knowledge management is currently one of the most important factors determining the company's market position. It depends not only on the skilful use of resources, but also on obtaining a synergistic effect. To manage knowledge, managers must possess not only the appropriate resources of knowledge, but also must have determined management structure with the assistance of the IT tools. Purpose of the article: The purpose of the article was to present how the modern enterprise knowledge management process is supported by information technology. For this purpose, was summarized selected indicators characterizing the use of ICT in various types of enterprises in the country. It assumed that it is important not only the equipment the companies with information technology tools, but also the degree of use of these tools. Methodology/methods: In this paper was used data published by the Central Statistical Office (GUS), Eurostat, the World Data Bank and Gartner Group. The analyzed indicators of ICT usage are presented in Polish enterprises divided according to the type of activity and size (small, medium, large). National indicators were related to the values occurring in the EU. Findings: Usage of ICT in Poland reaches ratios much lower than the average for the European Union. Large differences in the use of information technology occurs in individual groups of companies. Larger companies have reached a much higher degree of saturation of IT tools than smaller objects. For example, the number of Polish enterprises with computers was 94.7%, in the case of large companies it is 99.8%. Even greater discrepancy relates to access to the Internet. You may also notice differences in each province. Introduction of modern technologies related to computer science and computers (eg. cloud computing, big data, social media, e-commerce etc) enables effective knowledge management in companies. The indicators show that the management team appreciates the importance of knowledge and consistently invests for its development.
Keywords: D83; L63; O31; Q19; 330; knowledge management; information technology; IT; computer; internet users